Developing a Leadership and Practice Advancement Training Curriculum for Intern Pharmacists in Nigeria Using the ADDIE Model - Comfort Sariem; Ucheoma Nwizu; Jodie Malhotra (University of Minnesota Libraries Publishing, 2022)
The Problem: Leadership and clinical-pharmacy advancement training are lacking during post-graduate pharmacy internships in Nigeria. Objective: To design and develop a leadership and clinical-pharmacy advancement training curriculum for intern pharmacists. Innovation: The curriculum was designed to include leadership development, process improvement, and project management, with a culminating capstone project, using the analysis, design, development, implementation, and evaluation (ADDIE) model. Twelve intern-pharmacists were selected representing three pharmacy schools and four hospitals in Nigeria. Baseline assessments included previous exposure to module topics, beliefs, and level of comfort with module skills. Findings: The leadership curriculum was developed and tested on 12 intern pharmacists. Their average age±SD was 23.4±1.9 years and 7(58.3%) of the participants were males. The participants had received previous training in leadership (33.3%), project management (16.7%), and process improvement (16.7%).  In addition, 91.6% believed intern pharmacists could be leaders in advancing clinical pharmacy practice. Conclusion: The leadership and clinical-pharmacy advancement training curriculum was designed and developed using the ADDIE model for intern-pharmacists, who were highly prepared.